Is prostate sparing surgery a safe technique for radical cystectomy with orthotopic neobladder? [Ortotopi̇k mesane yapilan si̇stektomi̇de prostat korunmasi güveni̇li̇r bi̇r yöntem ṁiḋir?] - (:unkn) unknown (My University, 2005)
Introduction: Radical cystectomy is the standard treatment modality for invasive bladder cancer, and can be performed in patients with superficial bladder tumor refractory to intracavitary immuno/chemotherapy, recurrent high grade superficial bladder cancers and in the presence of carcinoma in-situ. There is a debate about prostatic dissection during radical cystoprostatectomy and neobladder in male patients. Some authors advocate leaving the prostatic apex or prostate for postoperative continence of the patient. As indicated in the literature, incidental prostate cancer can be detected in radical cystoprostatectomy specimens and this tumor can be located in the apical region of the prostate. Therefore, a prostate cancer focus could be left behind, if the surgeon does not perform prostatectomy or a proper apical dissection of the prostate. As a result some authors advocate performing prostatectomy with a wide apical resection of the prostatic apex. In this study we investigated the incidence and histomorphological properties of incidental prostate cancer in radical cystoprostatectomy specimens. Materials and methods: A total of 34 male patients who underwent radical cystoprostatectomy with a regular follow-up in Marmara University Department of Urology between 1991 and 2004, were included to the survey. All patients had a regular physical examination (including a rectal examination), laboratory examination (including prostate specific antigen) and radiological examination. Only one patient had a suspicious PSA value and had transrectal ultrasound guided prostate biopsy before surgery. The pathology of the specimens was evaluated by the Pathology Department of Marmara University Hospital. Results: Transitional cell carcinoma was detected in 85.4% of the patients whereas 8.8% of patients had squamous cell carcinoma, 2.9% had adenocarcinoma and 2.9% had small cell carcinoma. Only 10.3% of the bladder tumors were superficial. Prostate adenocarcinoma was detected in 11 (32.4%) patients. The mean age of the patients who had incidental prostate cancer was 59.7 years. The stage of prostate cancer was pT2a in 7 (20.6%) and pT2b in 4 (11.8%) patients. There were high grade PIN in 2 patients (5.9%) and low grade PIN in 1 (2.9%) patient. In 3 patients (27.2%) with incidental prostate cancer, there was a focus in the prostatic apex. Conclusion: In different studies, the incidence of incidental prostate cancer was reported to be 28-61%. In our study we detected incidental prostate cancer in 32.4% of the patients. There was no statistical significance between the age, preoperative PSA value and the incidence of incidental prostate cancer. The prognosis of the patient was not related with the presence of incidental prostate cancer, indeed the major prognostic factor of the patients was the primary bladder tumor. Although there is no statistically significant effect of incidental prostate cancer in patients' prognosis, there is no surveillance data of the patient who has residual incidental prostate cancer after radical cystoprostatectomy. As the incidence of incidental prostate cancer in radical cystoprostatectomy seemed to be high, it is better to remove the entire prostate including the prostatic apex during radical cystoprostatectomy for oncological principles.
Keywords: Cystoprostatectomy; Incidental diagnosis; Prostate cancer; Prostatic apex